Spinoza et le passé de la philosophie : un passé sans histoire ? - Philippe Danino (Astérion, 2012)
Spinoza’s relation to history is considered here as relation to the history of philosophy. The matter is not to research sources or influences of the doctrine, but to analyse the singular way that Spinoza as a philosopher recalls philosophy’s past. Can one legitimately call “historical” the use he makes of this past? Do evocation, correction or refutation reveal, in Spnoza’s writing, a form of historicity of philosophy? The idea put forward here is the following: the successive examining of philosophers, words, and of the motivations at work behind the writing of the Principia reveals, despite the appearances, no genuine history, but a variety of discursive strategies (drawing lines, narrating, constituting) meant to establish the elements of a “true” philosophy, and thereby to situate oneself through distanciation and the promotion of a singular thought.